Taxonomic investigations on the Braconinae fauna (Hymenoptera, Braconidae) in north-eastern Anatolian region, Turkey, with the description of a new species - Beyarslan, Ahmet (Zootaxa, 2016)
Adult specimens of Braconinae were collected from various habitats of Ardahan, Erzurum, Iğdır and Kars of the Turkish north-eastern Anatolian region between 2011 and 2014. In total, 87 species belonging nine genera are reported for the region among which 10 are recorded for the first time from Turkey: Bracon (Bracon) rhinchiti Greese, 1928, Bracon (Bracon) murgabensis Tobias, 1957, Bracon (Bracon) querceus Tobias, 1986, Bracon (Glabrobracon) karakumicus Tobias, 1967, Bracon (Lucobracon) hylobii Ratzeburg, 1848, Bracon (Lucobracon) irkutensis Telenga, 1936, Bracon (Orthobracon) longiantennatus Tobias, 1957, Bracon (Orthobracon) longigenis Tobias, 1957, Coeloides sordidator (Ratzeburg, 1844) and Glyptomorpha (Glyptomorpha) dispar Tobias, 1986. As well, Bracon (Bracon) selviae sp.n. is described. Thiss brings the total number of species of Turkish Braconinae recorded to 205. The known hosts of each species are also provided.